2014
DOI: 10.1186/2192-0567-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Alternative fuels from forest residues for passenger cars - an assessment under German framework conditions

Abstract: Background: Due to the available volumes, biogenic residues are a promising resource for renewable fuels for passenger cars to reduce greenhouse gas (GHG) emissions. In this study, we compare three fuels from forest residues under German framework conditions: biogenic electricity, substitute natural gas (SNG), and Fischer-Tropsch (FT) diesel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These processes contribute to 80% of his final result, so a larger GWP value is expected, which is the same as for the straw-based system in our study. On the other hand, Hurtig et al [14] reported a much lower result of 31 g CO 2 eq pkm -1 . This difference can be explained with the stages that are included in the system boundaries of their study and with the fact that their FT process' selectivity of diesel is approximately 80% of the FT raw products which is much higher than the selectivity data used for our study.…”
Section: Global Warming Potentialmentioning
confidence: 95%
See 2 more Smart Citations
“…These processes contribute to 80% of his final result, so a larger GWP value is expected, which is the same as for the straw-based system in our study. On the other hand, Hurtig et al [14] reported a much lower result of 31 g CO 2 eq pkm -1 . This difference can be explained with the stages that are included in the system boundaries of their study and with the fact that their FT process' selectivity of diesel is approximately 80% of the FT raw products which is much higher than the selectivity data used for our study.…”
Section: Global Warming Potentialmentioning
confidence: 95%
“…These authors modelled the GoBiGas demonstration plant; hence, they assumed larger transportation distances and they considered compressed SNG with a lower LHV (approximately 10%) than this study. On the other hand, Hurtig et al [14] reported a much lower GWP value of 40 g CO 2 eq km -1 . However, these authors do not explain what gasifier type they considered which makes any comparison difficult, but they did consider a commuter car; which is different from the car used in this study based on the fuel consumption rates, 0.4 kWh km -1 instead of 0.6 kWh km -1 (in ecoinvent database).…”
Section: Global Warming Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have addressed the energy consumption, environmental impact and emission of greenhouse gases (GHGs) of vehicles. These studies can be classified according to the fact that the analysis of the environmental impact and GHG emissions is based on the examination of the given type of fuel [5][6][7][8][9] or the comparison of vehicles using different fuels, such as conventional or renewable energy-based fuel [10][11][12][13][14]. Moreover, research on similar topics often takes into account other aspects, such as driving style [6], consumer preferences related to alternative fuels [15] charging behavior [16], the type of transportation [17][18][19] and the sustainability of transport systems [20,21].…”
Section: Introductionmentioning
confidence: 99%